2021
DOI: 10.3389/fvets.2020.609391
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Metabolic Alterations in Serum and Milk Whey Between Inactive Ovaries and Estrus Dairy Cows

Abstract: Inactive ovaries (IOs) affect the estrus cycle and timed artificial insemination (TAI) efficiency in dairy cows during early lactation. The objective of the experiment was to determine metabolic changes in the serum and milk whey of dairy cows with IO and estrus. Twenty-eight healthy postpartum Holstein cows in similar age, milk production, and body condition were selected at 30 days postpartum for tracking to 70 days postpartum, and estrus performance was recorded through Afi Farm® software. The ovarian statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Simi et al ( 2017 ) found that myo-inositol can improve ovarian function, oocyte quality, and embryo and pregnancy rates. In addition, Zhao et al ( 2020a ) also found that the content of myo-inositol was higher in the estrus cow serum than in cows with inactive ovaries. This is similar to the results obtained in this study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Simi et al ( 2017 ) found that myo-inositol can improve ovarian function, oocyte quality, and embryo and pregnancy rates. In addition, Zhao et al ( 2020a ) also found that the content of myo-inositol was higher in the estrus cow serum than in cows with inactive ovaries. This is similar to the results obtained in this study.…”
Section: Discussionmentioning
confidence: 96%
“…According to Butler et al ( 2006 ), pulsed secretion of gonadotropin-releasing hormone from the hypothalamus and luteinizing hormone from the pituitary gland were reported to be restrained by negative energy balance, thereby reducing the responsiveness of an ovary to luteinizing hormone. Previous research mainly focused on the effects of certain substances on follicular growth or ovarian activity in dairy cows (Song et al, 2019 ; Zhao et al, 2020a ). The literature on alterations in the percentage of yak estrus in estrus due to different feeding systems is not available.…”
Section: Introductionmentioning
confidence: 99%
“…Inactive ovaries are driven by a loss of periodic follicular activity and transient ovarian dysfunction ( 56 ). Nutritional status is generally recognized as a significant contributing factor to inactive ovaries, due to a close link between postpartum ovarian activity and energy balance ( 57 , 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that milk composition alters with the occurrence of estrus [ 8 , 9 , 10 ]. Importantly, the present study indicated that the days in relation to estrus had a significant effect on many infrared wavenumbers.…”
Section: Possible Use Of Milk Mir Spectra In the Reproductive Managementmentioning
confidence: 99%
“…Zebari et al [ 9 ] found that the concentration of acetic acid, valeric acid, caproic acid, and myristoleic were greater in milk on the day of estrus compared to the diestrus period, whereas the milk arachidonic acid concentration was greater in the diestrus period compared to the day of estrus. Zhao et al [ 10 ] showed that inactive-ovary cows compared with normal-estrus cows at 70 days postpartum had an increase in the milk whey of six different metabolites, including succinate, creatine phosphate, glycine, myo-inositol, glycolate, and orotate, and a decrease in the milk whey of seven metabolites, including alanine, creatinine, o-phosphorylcholine, lactose, taurine, galactose, and glucose-1-phosphate. These means that the changes of a large part of other milk composition elements due to estrus is unknown.…”
Section: Introductionmentioning
confidence: 99%